Cue rates and surfacing characteristics of sei whales (Balaenoptera borealis) in the Falkland Islands - R. Weir, Caroline; Taylor, Maria; A. Q. Jelbes, Pamela; Stanworth, Andrew (J. Cetacean Res. Manage., 2023)
The cue rate (CR: blows per whale per hour), surfacing characteristics and swim speeds of sei whales (Balaenoptera borealis) were quantified from focal follows carried out at Berkeley Sound (East Falkland) between January and May 2017 and off the west coast of West Falkland between February and April 2018. In Berkeley Sound, focal follows were conducted from Cape Pembroke lighthouse and from a small boat. In West Falkland all focal follows were conducted from a yacht. Thirty-seven focal follows of sei whale individuals or groups (2–5 individuals) were analysed to produce CRs ranging from 21.99 to 46.73, with a mean of 31.46 (SD = 5.12). There was no significant difference in the CRs observed from shore vs. boat platforms or between the two study areas. Maximum submergence times exceeding 13min were recorded from both individuals and groups. The durations of 51 whale surfacing events had a mean of 6.4s (SD = 1.7). The average swim speed during boat-based sei whale focal follows was 5.7kmh−1. The inter-breath intervals (IBIs) recorded from 13 solitary individuals ranged from 77.2 to 180.1s, with an overall mean of 118.6s (SD = 137.6). A combined approach incorporating IBI parameters and sequence pattern was used to classify 270 IBIs into surface dives (mean = 37.2s), intermediate dives (mean = 113.7s) and true dives (mean = 332.6s). Individuals showed marked variation in dive pattern, with some exhibiting clear cycles of true dives interspersed with surface bouts while others routinely took intermediate-duration dives interspersed by single surfacings. Sei whales in Berkeley Sound exhibited a higher proportion of surface dives than whales in West Falkland, and those surface dives were of lower mean and median IBI. Individual sei whales had surface bouts comprising a mean of 3.8 blows and a mean IBI of 33.4s. These are the first quantifiable data on surfacing-dive patterns and CRs for sei whales in the Falkland Islands and across the wider range of the species. The data have conservation and management relevance, including addressing availability bias for line transect and cue count abundance estimates, incorporation into vessel strike modelling, and understanding foraging behaviour.